Analysis of the Implementation of Retirement Entrepreneurship Training at the Jambi Province Human Resources Development Agency - Hamid Hamid (Jurnal Prajaiswara, 2021)
One of the program activities of BPSDM Jambi Province which is carried out every year is a training program for retired personnel, the aim is to prepare a number of alternative activities for officials who will enter retirement. This research is about the implementation process of retired entrepreneurial training. This research is a qualitative descriptive study, the informants in this study were the Head of the Jambi Province Human Resources Development Agency, the Head of the Core Technical Competency Development Division, the Heads of Sub-Heads, and the organizing committee. Data were obtained through interviews and activity report books and observations. The data analysis method is to use the data triangulation method, namely by making comparisons and discussions between the data obtained in the field. This research resulted that the implementation of entrepreneurial training Pra Purnabakti at BPSDM Jambi Province has been going well and quite systematically. The implementation process is divided into two parts, namely the planning process and the implementation process. This training planning activity is divided into two parts of planning, namely program planning, and implementation planning. Program planning consists of analyzing the needs of prospective participants of the Retired Entrepreneurship Training and compiling a module for the Retired Entrepreneurship Training program. Meanwhile, the planning for the implementation consists of determining the partners for the implementation of the training, the setting of the place, and the time of the implementation. For more success in the implementation of the training, it is hoped that the BPSDM will budget an adequate budget, due to the implementation of activities in the field.